The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1440-1584.2007.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recording and coding of smoking history for patients admitted to a regional hospital

Abstract: It is important that accurate information about the occurrence of smoking is available in hospital records both for treating health professionals and for coders for public health records, given that smoking is the leading cause of premature death in the developed world. 1,2 However, some reports have questioned the accuracy of medical record data and coding in a range of conditions and settings, so we undertook a small study in our institution. 3-5 Participants, methods and resultsA retrospective study was und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In a study of Nurse Unit Managers' report of provision of nicotine dependence treatment in all general hospitals in New South Wales, Australia, only 37% of respondents reported that all inpatients had their smoking status recorded, while few (17%) provided brief advice to quit or recommended NRT 13 . Audits of medical records in other Australian general hospitals in both urban and regional settings showed substantial errors in recording smoking status, 14,15 minimal provision of NRT and low prevalence of recorded smoking status on the discharge summary 16 …”
mentioning
confidence: 99%
“…In a study of Nurse Unit Managers' report of provision of nicotine dependence treatment in all general hospitals in New South Wales, Australia, only 37% of respondents reported that all inpatients had their smoking status recorded, while few (17%) provided brief advice to quit or recommended NRT 13 . Audits of medical records in other Australian general hospitals in both urban and regional settings showed substantial errors in recording smoking status, 14,15 minimal provision of NRT and low prevalence of recorded smoking status on the discharge summary 16 …”
mentioning
confidence: 99%
“…Decentralized approach is where all nurses (or other clinicians) are expected to provide interventions to their own patients [10]. …”
Section: Resultsmentioning
confidence: 99%
“…A recent Cochrane review showed that adding a tobacco use question to an EMR increases both the expectation that clinicians will intervene with tobacco and as well as clinician actions for treating tobacco use, and when interventions are provided, cessation increases [6] although meta-analyses show the most effective inpatient interventions are those where the intervention is initiated during hospitalization and followed up for at least one month post-discharge [9]. However, integrating tobacco use questions into EMRs does not ensure that cessation interventions will be provided due, at least in part, to the inconsistency of asking and documentation by different healthcare providers [10]. Moreover, if tobacco use data are being collected, challenges include various errors or inconsistencies such as tobacco status occurring in multiple places in a patient’s chart with discrepant information for the same visit, and usability of the data, which in turn, requires standardizing how tobacco use is coded (e.g., check boxes vs. open text fields) and determining a standard location in patients’ charts so data extraction programs can be designed [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If patients <55 years of age represent a relatively larger proportion of the ED population, the tobacco use rates would be expected to be higher than the general population. Even when tobacco use status is electronically recorded as part of standard practice in the ED, the quality of tobacco use data can be poor and data extraction can be difficult due to the inconsistency of asking and recording status by different healthcare providers, lack of standardization in terms of how tobacco use is coded and where it appears in the chart, and various errors such as tobacco status occurring in multiple places in a patient’s chart with discrepant information for the same visit [9]. …”
Section: Introductionmentioning
confidence: 99%